If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + 4(4y + 4) = 8 + 6(8 + -1y) Reorder the terms: -4y + 4(4 + 4y) = 8 + 6(8 + -1y) -4y + (4 * 4 + 4y * 4) = 8 + 6(8 + -1y) -4y + (16 + 16y) = 8 + 6(8 + -1y) Reorder the terms: 16 + -4y + 16y = 8 + 6(8 + -1y) Combine like terms: -4y + 16y = 12y 16 + 12y = 8 + 6(8 + -1y) 16 + 12y = 8 + (8 * 6 + -1y * 6) 16 + 12y = 8 + (48 + -6y) Combine like terms: 8 + 48 = 56 16 + 12y = 56 + -6y Solving 16 + 12y = 56 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 16 + 12y + 6y = 56 + -6y + 6y Combine like terms: 12y + 6y = 18y 16 + 18y = 56 + -6y + 6y Combine like terms: -6y + 6y = 0 16 + 18y = 56 + 0 16 + 18y = 56 Add '-16' to each side of the equation. 16 + -16 + 18y = 56 + -16 Combine like terms: 16 + -16 = 0 0 + 18y = 56 + -16 18y = 56 + -16 Combine like terms: 56 + -16 = 40 18y = 40 Divide each side by '18'. y = 2.222222222 Simplifying y = 2.222222222
| 12x-69=3x+102 | | -.666x(6-3z-7)= | | 23x-3y=5 | | 7-2(x-3)=5-8 | | -1-5=25 | | 6=-32 | | 7(3x-9)=11(4x+7) | | 11x-77=2x+175 | | 16+6=70-x | | 6x+7-2x=4(x+3) | | 2a^2-242=0 | | 7(x+6)-8=5(x-1) | | 22-4(-6.3)=12(-6.3)+126 | | (b+c-1)6= | | 2(-7x+6)-6x=-6 | | x^2+6x-188=0 | | x^2+6x-1880=0 | | y-3=7(x-1) | | -5x-8+4x=-6x-2 | | 25m^2+80m+64= | | -106+4x=141-9x | | 9+-24u+6=u+15 | | y=-4.9x^2+2x+21 | | (4t-q)(-3r)= | | 8x-7=32 | | 13*-9= | | (10+c)d= | | 1/2(180-x)=2(90-x)-12 | | x^2+9x-286=0 | | 19y+60=-6 | | 3-6x-16-20x=7-9x | | 2(2-x)=9x-84 |